AKIBAT HUKUM DARI PENYEBARAN IKLAN PADA MEDIA ELKETRONIK (DUNIA MAYA) YANG MEMUAT KONTEN PORNOGRAFI - Ikram Kalam Firdaus Rusli (Dinamika, 2019)
In the current era of globalization, the internet (cyberspace) plays an important role in society. The internet community easily gets any information that has been provided. Computer networks or what we often call internet (cyberspace) are a set of computers that are connected to one another and provide information by using a particular network, which aims to access information such as web browsing, which can be called the world market. virtual because in the internet sellers and buyers can be reunited, just as when we buy a product in a store, sellers and buyers immediately interact and make purchases and transactions directly or face to face with the sellers and buyers.Legal consequences of the spread of advertisements on electronic media (the virtual world) that contain pornographic content in terms of positive law.